Syntheses of quinolines as neural protective reagents and progress towards total synthesis of (+) - myriceric acid A - Lu, Jianyu (Kansas State University, 2014)
The first chapter of this dissertation introduces and discusses the syntheses of a series of substituted quinolines as glycogen synthase kinase-3[beta] (GSK-3[beta]) inhibitors. GSK-3[beta] is highly associated with Alzheimer’s disease (AD), and it is suggested that inhibition of this enzyme could alleviate the symptoms of AD. Total 16 novel substituted quinolines were designed and synthesized, and their bio-activities were evaluated on MC65 cell protection assay. Four of the most active compounds were selected to test their enzyme inhibitory activities on GSK-3[beta] and protein kinase C assays. Among these compounds, 4-{[6-methoxy-4-methyl-5-(3-(trifluoromethyl)phenoxy)quinolin-8-ylamino]methyl} phenol (1.5) shows the highest MC65 cell protection and GSK-3[beta] enzyme inhibitory activities and potential enzyme specificity. Structure-activity relationship (SAR) was built as well, and the binding mode was simulated via computational method to interpret the observed SAR. Although additional bio-evaluation is needed, compound 1.5 is a promising lead compound for the development of more active and less toxic drug for the conteraction of AD. The second chapter introduces the progress on the total synthesis of myriceric acid A. Myriceric acid A is a triterpene-type natural product which was isolated from the young twigs of Myrica cerifera. It is a non-peptide endotheline-1 (ET-1) receptor antagonist. The total synthesis of this natural product started from the stereoselective synthesis of bicyclic intermediate (R)-5,8a-dimethyl-3,4,8,8a-tetrahydronaphthalene-1,6(2H,7H)-dione [(-)-2.28]. Then a new method was developed to enatioselectively synthesize the tricyclic intermediate (4aR,8R,8aR)-8-(tertbutyldimethylsilyloxy)-1,4a,8a-trimethyl-4,4a,4b,5,6,7,8,8a,9,10-decahydro phenanthren-2(3H)-one [(+)-2.72] which used the synthesized optically-pure (4aR,5R)-5-(tertbutyldimethylsilyloxy)-1,4a-dimethyl-4,4a,5,6,7,8-hexahydronaphthalen-2(3H)-one [(-)-2.53] derived from (-)-2.28 and [alpha]-trimethylsilylvinyl ethyl ketone via a cascade reductive Michael addition – aldol condensation reaction. After functional group inter-conversion, the desired tricyclic intermediate (4a'S,8a'R)-1',1',4a',8a'-tetramethyldecahydro-1'H-spiro[[1,3]dioxolane-2,2'-phenanthren]-8'(3'H)-one [(-)-2.33] was synthesized. An intramolecular cascade Michael addition-aldol condensation reaction was designed to construct the triterpene-skeleton of myriceric acid A, and the desired starting material for this reaction was prepared with the trimethyl{(4a'R,8a'R)-1',1',4a',8a'-tetramethyl-3',4',4a',4b',5',6',8a',9',10',10a'-decahydro-1'Hspiro[(1,3)dioxolane-2,2'-phenanthrene]-8'-yloxy}silane [(-)-2.81] and 3,3-dimethyl-7-oxooctanal (2.46) via Mukaiyama aldol condensation reaction. The resulting pentacyclic compound was further transformed to the desired ester (6a'R,8a'R,12a'S,12b'R,14b'R)-ethyl 4',4',6a',11',11',14b'-hexamethyl-8'-oxo-2',4',4a',5',6',6a',8',8a',9',10',11',12',12a',12b',13',14',14a',14b'-octadecahydro-1'H-spiro[(1,3) dioxolane - 2, 3 '- picene]-8a'-carboxylate (-)-2.106. The further investigation on total synthesis of myriceric acid A will be pursued in future.
Keywords: Quinolines; Total synthesis; GSK-3 beta; Myriceric acid A; Chemistry (0485)